2002
DOI: 10.1161/01.atv.0000029968.34056.94
|View full text |Cite
|
Sign up to set email alerts
|

Factors Contributing to Individual Propensity for Arterial Thrombosis

Abstract: Objective-Occurrence of arterial thrombosis secondary to vascular disease in an individual is not easily predicted. After establishing that this poor predictability arises at least in part from an intrinsic thrombosis propensity of the individual, we sought to determine whether the propensity for arterial thrombosis is governed by blood or arterial wall factors. Methods and Results-To evaluate the variability arising from the blood, autologous 111 In-labeled platelet deposition was measured after high-shear pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
1
2

Year Published

2004
2004
2010
2010

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 36 publications
2
19
1
2
Order By: Relevance
“…Previous studies utilizing the carotid injury model have specifically considered thrombolysis at sites of arterial injury (4) and found a specific contribution to fibrinolysis. This observation is confirmed by a study (14) that demonstrates that arterial thrombosis is more influenced by blood components than elements within the arterial wall. Thus in this setting of carotid injury, the secondary effect of NO deficiency, namely, the enhanced release of t-PA from endothelial Weibel-Palade bodies, is of greater relevance than the release of NO from the endothelium.…”
Section: Discussionsupporting
confidence: 59%
“…Previous studies utilizing the carotid injury model have specifically considered thrombolysis at sites of arterial injury (4) and found a specific contribution to fibrinolysis. This observation is confirmed by a study (14) that demonstrates that arterial thrombosis is more influenced by blood components than elements within the arterial wall. Thus in this setting of carotid injury, the secondary effect of NO deficiency, namely, the enhanced release of t-PA from endothelial Weibel-Palade bodies, is of greater relevance than the release of NO from the endothelium.…”
Section: Discussionsupporting
confidence: 59%
“…Using porcine models of thrombus deposition onto excised vessel segments, Karnicki et al found that thrombus deposition varied strongly with individual blood donors and relatively little with the source of the aortic segment. 97 Together, these studies suggest that in contrast to thrombus initiation, the primary regulators of thrombus growth may come from the blood and not the vessel wall, and that these regulators may vary significantly among individuals.…”
Section: Temporal and Spatial Considerations In Thrombus Growthmentioning
confidence: 95%
“…Vulnerable blood (prone to thrombosis)plays an important roleinthe outcome of CAD (7).The importanceofthe coagulation system underlying plaque complications hasbeen experimentallyaddressed by Karnicki et al whodemonstrated in a porcine modelt hat blood factorsm ust have am ajor role in thrombus propagation (12). Moreover, it hasa lso been establishedt hat after an episode of unstable angina or AMI, ah igh proportion of patients showbiochemical signs of coagulation activation in their blood (13)(14)(15)(16),which mayhaveagreat impact in termsofrecurrence and long-termmortality (17).…”
Section: Introductionmentioning
confidence: 99%